2016
DOI: 10.5902/1980509825105
|View full text |Cite
|
Sign up to set email alerts
|

DECOMPOSIÇÃO DA SERAPILHEIRA FOLIAR DE FLORESTA NATIVA E PLANTIOS DE <i>Pterogyne nitens</i> E <i>Eucalyptus urophylla</i> NO SUDOESTE DA BAHIA

Abstract: RESUMOO processo de decomposição regula o acúmulo de serapilheira e a ciclagem de nutrientes em ecossistemas florestais, sendo fundamental para sua manutenção. O objetivo deste trabalho foi avaliar a dinâmica de decomposição foliar em uma Floresta Estacional Semidecidual Montana e em plantios homogêneos de Pterogyne nitens Tul. e de Eucalyptus urophylla S. T. Blake, localizados no município de Vitória da Conquista, Bahia, Brasil. Para avaliação da decomposição, folhas recém-caídas foram coletadas, secas em est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 5 publications
4
19
0
6
Order By: Relevance
“…The percentage of remaining biomass in the litter bags still not decomposed was similar to that found in an E. urophylla plantation in the state of Bahia, in which Pinto et al (2016) verified rates of 73.56% at 180 days after the beginning of the experiment. In the state of São Paulo, Bachega et al (2016) at 180 days after experiment initiation, it was 63.00% of the leaf biomass remaining in the litter bags in an E. grandis planting.…”
Section: Leaf Decompositionsupporting
confidence: 81%
See 1 more Smart Citation
“…The percentage of remaining biomass in the litter bags still not decomposed was similar to that found in an E. urophylla plantation in the state of Bahia, in which Pinto et al (2016) verified rates of 73.56% at 180 days after the beginning of the experiment. In the state of São Paulo, Bachega et al (2016) at 180 days after experiment initiation, it was 63.00% of the leaf biomass remaining in the litter bags in an E. grandis planting.…”
Section: Leaf Decompositionsupporting
confidence: 81%
“…In the present study, leaf biomass decay was evidenced only after 90 days from experiment initiation. Pinto et al (2016) reported that sugar content was the first to be decomposed over the first three months after leaves fell on the ground; however, lignin content tends to remain constant over a much longer period of time (COSTA et al, 2005). After the first quarter, most of the strongest structures rich in lignin, cellulose, waxes and tannins, such as ribs and petioles, still remain, reducing the rate of decomposition (CARVALHO et al, 2009;LIMA et al, 2015b ;VIERA et al, 2014b).…”
Section: Leaf Decompositionmentioning
confidence: 99%
“…Mendonça et al (2015) assessed different grass species grown in consortium system with maize and found higher N leach rates at the first 30 DAI, as well as subsequent stabilization of it. It was justified by Perin et al (2010) and Pinto et al (2016), who found N release correlated to C release (decomposition of residues) in two phases: i) fast decomposition of structural components of easy decomposition (< C/N); ii) slow decomposition of more resistant materials (> C/N).…”
Section: /8mentioning
confidence: 99%
“…The decomposition process regulates burlap accumulation and nutrient cycling in forest ecosystems, and is fundamental for its maintenance (Pinto et al, 2016). The decomposition of canopy structures and microorganisms comprise the main source of nutrients for the forest ecosystem.…”
Section: Introduction and Objectivesmentioning
confidence: 99%